IMPACT OF RESIDUAL SUBRETINAL FLUID VOLUMES ON TREATMENT OUTCOMES IN A SUBRETINAL FLUID–TOLERANT TREAT-AND-EXTEND REGIMEN. Issue 11 (November 2021) - Grechenig, Christoph; Reiter, Gregor S.; Riedl, Sophie; Arnold, Jennifer; Guymer, Robyn; Gerendas, Bianca S.; Bogunović, Hrvoje; Schmidt-Erfurth, Ursula
Abstract : Purpose: To investigate associations between residual subretinal fluid (rSRF) volumes, quantified using artificial intelligence and treatment outcomes in a subretinal fluid (SRF)–tolerant treat-and-extend (T&E) regimen in neovascular age-related macular degeneration. Methods: Patients enrolled in the prospective, multicenter FLUID study randomized in an SRF-tolerant T&E regimen were examined by spectral-domain optical coherence tomography and tested for best-corrected visual acuity (BCVA). Intraretinal fluid and SRF volumes were quantified using artificial intelligence tools. In total, 375 visits of 98 patients were divided into subgroups: extended intervals despite rSRF and extended intervals without fluid. Associations between BCVA change, SRF volume, subgroups, and treatment intervals were estimated using linear mixed models. Results: In extended intervals despite rSRF, increased SRF was associated with reduced BCVA at the next visit in the central 1 mm (−0.138 letters per nL; P = 0.014) and 6 mm (−0.024 letters per nL; P = 0.049). A negative association between increased interval and BCVA change was found for rSRF in 1 mm and 6 mm (−0.250 and −0.233 letter per week interval, respectively; both P < 0.001). Extended intervals despite rSRF had significantly higher SRF volumes in the central 6 mm at the following visit ( P = 0.002). Conclusion: Artificial intelligence–based analysis of extended visits despite rSRF demonstrated increasing SRF volumes associated with BCVA loss at the consecutive visit. This negative association contributes to the understanding of rSRF volumes on treatment outcomes in neovascular age-related macular degeneration. Abstract : Quantitative artificial intelligence–based analysis of extended visits despite residual subretinal fluid in a subretinal fluid–tolerant treat-and-extend treatment regimen shows that increasing residual subretinal fluid volumes have a negative impact on visual function at the consecutive visit. This highlights the importance of precise and quantitative measurements of fluid volumes in neovascular age-related macular degeneration.